Empire of love histories of France and the Pacific - Matsuda, Matt K. (Oxford University Press, 2005)
This title studies the creation of an 'Empire of Love' in the Pacific and the interconnections between culture and imperial power in the 19th and 20th centuries. It examines the European presence in such contested territories as New Caledonia, and Tahiti, and encounter and conflict in Panama and Indochina.